Comparing Between Makassarese and English Adverbs of Time - Abd.Rajab; Pratomo Widodo; Wahyuddin Rauf (CV. Eureka Murakabi Abadi, 2022)
Contrastive analysis is very important for learning second language acquisition because with knowing the difference and the similarities L1 and L2 that the learner became easy to learn the L2. The research aimed to analyze the simaliries and the differences between Makassarese as L1 and English as L2 in adverbs of time. This study applied a qualitative study to cover the problem. First, the researcher collected the data from books on Makassarese grammar, Buginese Grammar, English grammar and from the researcher as the native speaker of Makassarese. Second, the researcher identified them in every type of adverbs. At last, data were analyzed from the data collection. The finding of the research indicates that; the researcher found all of the adverbs. After analyzing the data, the researcher found the similarities and the differences with comparing both of them. Thus, the researcher can find the Similarities based on functions both Makassares as L1 and English as L2, to explain some wors namely, verbs, adjectives and other adverbs. Based on the position, both can be placed in front, middle and end. Differences based on functions can be found that English has sentence sentences that use many words ending in -ed + -ly. Based on tenses, in English context, the verbs should be changed based on the tenses, for example, go (present V1+es/s), went (Past Verb2), and go (Future will/shal+V1). Besides that, the researcher can know without an adverb of time in the sentence when the situation is happening only see the verb in the sentence. But in Makassares context, the researcher cannot identify the sentence without adverb of time when the action is happening.